2019
DOI: 10.3390/ijerph16203877
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Problematic Internet Use and Its Impact on Adolescents’ Health-Related Quality of Life

Abstract: The internet has been a breakthrough for adolescents in many ways, but its use can also become dysfunctional and problematic, leading to consequences for personal well-being. The main objective is to analyze profiles related to problematic internet use and its relationship with health-related quality of life (HRQoL). An analytical and cross-sectional study was carried out in a region of northern Spain. The sample comprised 12,285 participants. Sampling was random and representative. Mean age and standard devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 63 publications
4
40
0
15
Order By: Relevance
“…In order to verify the research hypotheses, this work proposed a conceptual model including those dimensions that might potentially affect student well-being. The model was devised on the basis of previous relevant works in the literature (Zimmermann and Iwanski, 2014;Gascó et al, 2018;Machimbarrena et al, 2019;Do et al, 2020). The conceptual model was assessed by applying component-based partial least squares structural equation modeling (PLS-SEM), designed to determine the values of the variables in relation to the predicted purpose (Chin, 1998).…”
Section: Measures and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to verify the research hypotheses, this work proposed a conceptual model including those dimensions that might potentially affect student well-being. The model was devised on the basis of previous relevant works in the literature (Zimmermann and Iwanski, 2014;Gascó et al, 2018;Machimbarrena et al, 2019;Do et al, 2020). The conceptual model was assessed by applying component-based partial least squares structural equation modeling (PLS-SEM), designed to determine the values of the variables in relation to the predicted purpose (Chin, 1998).…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…Digital society provides numerous opportunities but despite the implied advantages it also brings risks, especially for younger people (Machimbarrena et al, 2019); indeed, use of the internet can become problematic, leading to consequences for personal wellbeing. In particular, young people are continually increasing their smartphone use (Humphreys et al, 2013) and internet addiction has become ubiquitous (Haverlag, 2013;Yam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Because playing video games is a highly valuated and time-consuming activity for adolescents, mental health professionals have acquired an interest in Internet Gaming Disorder (IGD)'s effects on well-being. Research has demonstrated that adolescents' quality of life would decrease if Internet access was limited [1], that problematic internet use correlates negatively and significantly with health-related quality of life [2], and that Chinese adolescents with problematic Internet use (PIU) have lower scores on total and all dimensions of life satisfaction measures [3] and lower well-being [4] than non-PIU adolescents. A study of elementary school children showed that children with pathological and maladaptive Internet use exhibited more severe depression and lower health-related quality of life [5].…”
Section: Contextmentioning
confidence: 99%
“…This study allowed us to examine the existence of four profiles of different types of conflicts related to internet use (intrapersonal and interpersonal), similar to the four profiles of internet use (from non-problematic use to severe problematic use) evidenced in studies on problematic internet use [ 51 ]. Previous studies showed the existence of three clusters for problematic internet use on the CERI scale based on low, moderate, or high scores between the ages of 11 and 25 [ 22 , 43 ].…”
Section: Discussionmentioning
confidence: 99%